Grit and peer relationships in early adolescence: A person-centered approach. (July 2020) - Lan, Xiaoyu
Although a burgeoning body of research has illustrated the association of grit with academic and psychosocial functioning in adolescence, little is known about how adolescents with differing grit profiles may diverge in regard to peer relationships (i.e., perceived popularity and friendships). Guided by the dynamic interactionism framework, the current study, using a person-centered approach, explores grit profiles of Chinese early adolescents and examines whether these profiles exhibit mean differences in perceived popularity and friendships. A total of 1, 150 early adolescents aged from 10 years to 13 years (53.4% male) were involved in this study; participants were asked to complete self-report questionnaires concerning grit and self-perception of friendships and complete peer nominations within each classroom in terms of perceived popularity. A latent profile analysis revealed five grit profiles based on two facets of grit (i.e., perseverance and consistency). Moreover, multivariate analysis of covariance—controlling for age, gender, and socioeconomic status—showed that early adolescents who scored higher on both perseverance and consistency were nominated as more popular individuals than those with low-to-moderate perseverance and low consistency. In contrast, perseverance was more essential than consistency in determining greater self-perception of friendships. To summarize, the current study suggests that both perseverance and consistency are pivotal in terms of perceived popularity, whereas perseverance is critical in regard to the self-perception of friendships.